Environmental criminology : spatial analysis and regional issues - Leonard, Liam (Bingley, U.K. : Emerald Publishing Limited, 2017)
Environmental Criminology: Spatial Analysis and Regional Issues combines various academic perspectives to provide a multi-disciplinary approach to examining environmental criminology. Using sociological, criminological, anthropological, historical and media analysis, this volume examines local and regional issues in crime. The interdisciplinary nature of the collection makes the book ideal for students or researchers who wish to expand their approach to environmental criminology.
Prelims -- Framing injustice in green criminology: activism, social movements and geography -- Anthropology at the Red-Green Crossroads -- The Ferguson shooting, 2014: A spatial and media analysis -- Spatial patterns of mass shootings in the United States, 2013 - 2014 -- Homeless demography in Los Angeles County -- Police culture, gender and crime in the Irish Free State -- A spatial analysis of crime:'The Wire' and depictions of urban crime -- Toward a spatial analysis of methamphetamine in North America -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Crime -- Regional disparities -- Case studies; Criminology -- Social aspects